IDENTIFIKASI PERMASALAHAN PENERAPAN RESTORATIVE JUSTICE DI KEJAKSAAN NEGERI GROBOGAN - Gunanto, Muhammad Adhistiya Wahidakbar (Criminal Law Section Faculty of Law Universitas Sebelas Maret, 2023)
This research was conducted with the aim of knowing the settlement of cases with the principle of justice regarding restorative approaches and the implementation of the resulting agreement at each level of examination. As long as the restorative justice process takes place and after restorative justice is carried out, social counselors are required to provide guidance and supervision. Restorative justice is not carried out within the time specified in the agreement. This involves a process in which all parties at risk of a particular crime jointly try to collectively resolve how to deal with the aftermath of a crime and its implications in the future. The restorative justice policy in cases that occur at the Grobogan district attorney's office which acts in accordance with the role of law enforcement officials, especially the prosecutor's office which is part of the criminal justice subsystem, is obliged to seek settlement by prosecutor who handle all cases. The perspective of restorative justice from the aspect of judicial administration is to reduce the accumulation of cases. However, it can be stated the urgency of the need to settle minor criminal cases when viewed from a restorative justice perspective, because society dominates the development of the legal system. based on the concept of restorative justice Restorative justice does not only discuss who wins and who loses which can trigger hostility/resistance (adversarial system), the restorative justice process emphasizes a dialogue facility between all parties affected by crime including victims, perpetrators, supporters, and society as a whole.